AMANDEMEN DALAM SEJARAH HUKUM ISLAM; STUDI TERHADAP PERUBAHAN FATWA IBNU QAYYIM AL-JAUZIYAH - Gunawan, Syafri (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
This paper describes the amendments that occur in Islamic law, which in Islam also recognizes amendments or more familiarly called changes in legal fatwas due to the development of the times so that the law develops according to its flexible nature. To see the process and form of this amendment, the author uses the literature study method, namely by browsing the literature that talks about the topics discussed.The findings in the search, that it is not only positive Indonesian law that recognizes the concept of amendment, but long ago Islamic law has talked about amendments, only the terms are different, but the goal remains the same, namely developing a rule so that it is more detailed to reach all aspects of human life.